PENGARUH RETURN ON ASSET (ROA) DAN RETURN ON EQUITY (ROE) TERHADAP PERTUMBUHAN LABA PADA PT. KALBE FARMA TBK PERIODE 2009 – 2019. - Eman Singgih (Universitas Insan Pembangunan Indonesia, 2022)
This study aims to determine the Effect of Return On Assets (ROA) and Return On Equity (ROE) on Profit Growth of PT Kalbe Farma Tbk for the period 2009-2019, either partially or simultaneously. This type of research is descriptive quantitative with secondary data type from the financial statements of Kalbe Farma Tbk. the period 2009-2019. The implementation of this research was carried out from November 2020 to August 2021 where the research was conducted on the Jakarta Stock Exchange. The results of the study partially show that Return on Assets (ROA) has a positive and significant effect on Profit Growth. Return On Equity (ROE) has a positive and significant effect on Profit Growth, and simultaneously Return On Assets (ROA) and Return On Equity (ROE) jointly have a significant effect on Profit Growth. It is proven by the R Square value of 0.276 which means that 27.60% of the Profit Growth variable can be explained by the independent variables, namely Return On Assets (ROA) and Return On Equity (ROE), while the remaining 72.40% is explained by other variables not included in this study. Given the limitations in the study, the authors suggest that in future research, if you want to conduct research with a similar theme, you should extend the research period so that the effect can be seen from a longer period of time and enhances the power of the test and also uses a wider research object. Keywords: Return On Assets (ROA), Return On Equity (ROE) and Profit Growth